1986
DOI: 10.1002/prot.340010304
|View full text |Cite
|
Sign up to set email alerts
|

A very short peptide makes a voltage‐dependent ion channel: The critical length of the channel domain of colicin E1

Abstract: Cleavage of colicin E1 molecules with a variety of proteases or with cyanogen bromide (CNBr) generates COOH-terminal fragments which have channel-forming activity similar to that of intact colicin in planar lipid bilayer membranes. The smallest channel-forming fragment obtained by CNBr cleavage of the wild-type molecule consists of the C-terminal 152 amino acids. By the use of oligonucleotide-directed mutagenesis, we have made nine mutants along this 152 amino acid peptide, in which an amino acid was replaced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Western blot analysis with anti-HA antibody, for mutants II and III, or with anti-FLAG, for mutants IV and V, revealed that the truncated polypeptides were missing the C-terminal end, including the HA or FLAG epitope. Because C-terminal deletions eliminate the channelforming and bactericidal activities of channel-forming colicins, the truncated polypeptides should not have affected our measurements (23,24). Mutant HA-I, in contrast, was not degraded.…”
Section: Methodsmentioning
confidence: 98%
“…Western blot analysis with anti-HA antibody, for mutants II and III, or with anti-FLAG, for mutants IV and V, revealed that the truncated polypeptides were missing the C-terminal end, including the HA or FLAG epitope. Because C-terminal deletions eliminate the channelforming and bactericidal activities of channel-forming colicins, the truncated polypeptides should not have affected our measurements (23,24). Mutant HA-I, in contrast, was not degraded.…”
Section: Methodsmentioning
confidence: 98%
“…Although the isolated C-terminal fragment by itself is competent to insert into membranes (16), and pore-forming domains of other colicins exhibit pore-forming activities in vitro (17,(43)(44)(45), all three domains are required for recognition, translocation, and pore formation at intact cells in vivo. It appears that mutual interactions between different regions of colicin B help to maintain the translocation and the poreforming domains in less stable but functionally competent conformations.…”
Section: Structural and Functional Characteristics Of Colicin B Andmentioning
confidence: 99%
“…The colicin El COOHterminal domain is significantly similar to colicin A [1,5 -71. The minimum size of this domain that is competent for channel function is under debate [8]. However, it is clear that a colicin El COOH-terminal fragment of 152 residues is competent for channel function [9].…”
mentioning
confidence: 99%